2007
DOI: 10.1016/j.ejpain.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and sensory changes after direct ischemia‐reperfusion injury in rats

Abstract: Complex regional pain syndromes (CRPS) are disabling pain syndromes that can develop after trauma or minor tissue injury affecting a limb. Characteristics of CRPS are sensory signs and symptoms, autonomic abnormalities, trophic changes and an impaired motor function. Pathophysiological mechanisms for the development of CRPS are still a matter of investigation. Based on clinical data and investigations of CRPS patients it is hypothesized that tissue hypoxia and inflammation are important for the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
12
2
2
Order By: Relevance
“…Unlike previous studies (Coderre et al, 2004;Ludwig et al, 2006), in the present study we did not observe mechanical allodynia in the contralateral hind paw. This observation could be due to the fact we always tested the contralateral hind paw prior to the ipsilateral hind paw and may have avoided acute spinal sensitization following mechanical stimulation of the hypersensitive hind paw.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Unlike previous studies (Coderre et al, 2004;Ludwig et al, 2006), in the present study we did not observe mechanical allodynia in the contralateral hind paw. This observation could be due to the fact we always tested the contralateral hind paw prior to the ipsilateral hind paw and may have avoided acute spinal sensitization following mechanical stimulation of the hypersensitive hind paw.…”
Section: Discussioncontrasting
confidence: 56%
“…Coderre et al (2004) showed that a 3 h-ischemia/ reperfusion of the hind paw induced long-term (4 weeks) mechanical and cold hypersensitivity (known as chronic post-ischemia pain), which was reduced by free radical scavengers. Mechanical hypersensitivity is also observed after 3 h-occlusion of the femoral artery (Ludwig et al, 2006), although sham rats were also affected.…”
Section: Introductionmentioning
confidence: 81%
“…In the present study the peripheral nerve has been targeted for induction of vasculatic neuropathy in rats by the process of femoral artery I/R. The event of femoral artery I/R process has been well documented for the induction of the neuro-inflammation, neuronal excitability and enhancement of pain sensation (Ludwig et al, 2007). The production of reactive oxygen species and reactive nitrogen species (ROS/RNS) in severe oxidative stress conditions leads to loss of membrane integrity and structural or functional changes (Gholami et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Conspicuously, CRPS sensory abnormalities may spread in a hemisensory manner [3] or even contralaterally [4]. No generally accepted animal model of CRPS I exists, but very recently an ischemia-reperfusion injury model reproduced some changes observed in humans [5] (but see [6]). …”
Section: Introductionmentioning
confidence: 99%